Electrical Control of Antiferromagnetic CuMnAs - Amin, O.J. (2022)
Antiferromagnetic (AF) materials are expected to become the primary components in next generation magnetic memory devices, due to their ultrafast spin dynamics, robustness against external magnetic fields, and downsize scalability. The most promising candidate material, so far, is tetragonal CuMnAs - a semimetal AF with the required crystal symmetry to host current-induced N´eel spin-orbit torque. This offers a novel way to efficiently manipulate the AF order using electrical pulses.